2002
DOI: 10.1021/jo011082s
|View full text |Cite
|
Sign up to set email alerts
|

1,2- vs 1,4-Addition of Acylbenzotriazoles to α,β-Unsaturated Aldehydes and Ketones. A Novel Route to 3-Alkyl-4,6-diaryl-3,4-dihydropyran-2-ones

Abstract: Lithiation of aliphatic 1-acylbenzotriazoles with subsequent reaction with alpha,beta-unsaturated ketones and aldehydes affords either 3,4,6-trisubstituted 3,4-dihydropyran-2-ones or 1,3-dienes depending on the carbonyl reagent used. Substituent effects on product yield and isomer ratio are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…A similar addition of anions derived from acylbenzotriazoles 949 to cinnamaldehydes provide unstable β-lactones that undergo spontaneous ring opening and decarboxylation to dienes 952 (a mixture of ( E,E ) and ( E,Z ) isomers). However, in the case of chalcones, the nucleophilic attack goes on the β-carbon atom to yield 3,4-dihydropyran-2-ones 953 , via intramolecular acylation of the oxygen atom in anionic intermediates 950 <2002JOC3104> .
Scheme 157
…”
Section: Reactivity Of Substituents Attached To Ring Nitrogensmentioning
confidence: 99%
“…A similar addition of anions derived from acylbenzotriazoles 949 to cinnamaldehydes provide unstable β-lactones that undergo spontaneous ring opening and decarboxylation to dienes 952 (a mixture of ( E,E ) and ( E,Z ) isomers). However, in the case of chalcones, the nucleophilic attack goes on the β-carbon atom to yield 3,4-dihydropyran-2-ones 953 , via intramolecular acylation of the oxygen atom in anionic intermediates 950 <2002JOC3104> .
Scheme 157
…”
Section: Reactivity Of Substituents Attached To Ring Nitrogensmentioning
confidence: 99%
“…In 1997, Kobayashi12 reported the first example, followed by Katritzky 13. Mukayama utilized chiral quaternary ammonium phenoxides derived from chinchona alkaloids in a new organocatalysed Michael process under phase‐transfer conditions 14.…”
Section: Introductionmentioning
confidence: 99%
“…N -Acyl derivatives of benzotriazole (COBt) are known as powerful acylating agents and have found widespread application in organic synthesis . Although the strong electron-withdrawing properties of the Bt group can significantly increase the acidity of hydrogen atom at the α-position, only a few studies focused on the α-functionalization of COBts. , Katritzky et al reported a fascinating formation of polysubstituted 3,4-dihydropyran-2-ones or 1,3-dienes by intramolecular cyclization of lithium enolates of N -acylbenzotriazoles to α,β-unsaturated carbonyl compounds in good yields and up to 20:1 dr . Barbas et al found the first organocatalyzed asymmetric α-functionalization of 4-nitrobenzyl COBt to yield the product with low chiral induction (20% ee).…”
mentioning
confidence: 99%
“…33 Although the strong electron-withdrawing properties of the Bt group can significantly increase the acidity of hydrogen atom at the αposition, only a few studies focused on the α-functionalization of COBts. 34,35 yields and up to 20:1 dr. 36 Barbas et al found the first organocatalyzed asymmetric α-functionalization of 4-nitrobenzyl COBt to yield the product with low chiral induction (20% ee). We report herein an efficient organocatalyzed asymmetric cascade reaction with N-TFA glycine Bt and α,βunsaturated aldehydes as the substrates affording chiral 3,4,6-trisubstituted tetrahydro-2H-pyran-2-ones in up to 65% overall yield and 99% ee (Scheme 1E).…”
mentioning
confidence: 99%